2022
DOI: 10.3390/antiox11050851
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Angiogenic Effects of Natural Antioxidants Extracted from Mango Leaf, Olive Leaf and Red Grape Pomace over Endothelial Colony-Forming Cells

Abstract: Cardiovascular diseases remain the leading cause of death worldwide, mainly triggered by the formation of atherosclerotic plaques that reduce blood flow. Angiogenic cell therapy based on endothelial colony forming cells (ECFCs) constitutes a promising alternative to promote vascular revascularization; however, under the oxidative environment that prevails in ischemic areas, these cells become impaired. Thus, it is necessary to investigate strategies to enhance their regenerative properties. Antioxidant substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…However, ECFCs need to be pre-stimulated in vitro with antioxidant substances to enhance this ability. Recent studies have shown that anthocyanin -phenolic acid rich in grapes-promotes the pro-angiogenic effect of these cells [66] and that resveratrol enhances the angiogenesis of cord vein endothelial cells [67]. Moreover, resveratrol also induced the differentiation of vascular progenitor cells into endothelial cells critical for new vessel formation [66].…”
Section: Cardiovascular Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ECFCs need to be pre-stimulated in vitro with antioxidant substances to enhance this ability. Recent studies have shown that anthocyanin -phenolic acid rich in grapes-promotes the pro-angiogenic effect of these cells [66] and that resveratrol enhances the angiogenesis of cord vein endothelial cells [67]. Moreover, resveratrol also induced the differentiation of vascular progenitor cells into endothelial cells critical for new vessel formation [66].…”
Section: Cardiovascular Propertiesmentioning
confidence: 99%
“…Recent studies have shown that anthocyanin -phenolic acid rich in grapes-promotes the pro-angiogenic effect of these cells [66] and that resveratrol enhances the angiogenesis of cord vein endothelial cells [67]. Moreover, resveratrol also induced the differentiation of vascular progenitor cells into endothelial cells critical for new vessel formation [66]. In addition to the pro-angiogenic effects induced by the bioactive compounds present in grape pomace, they could directly reduce atherosclerosis, as demonstrated by several experimental studies.…”
Section: Cardiovascular Propertiesmentioning
confidence: 99%
“…Second, the inert atmosphere generates supercritical CO 2 , which avoids the oxidation of compounds. Third, it promotes the extraction of lipidic and other low-polar compounds that can facilitate plasticizing effect in the film-forming process, and finally, the low temperature used in the process avoids the loss of bioactivity of the extracts [51]. Taking all these benefits into consideration, ESE was employed to obtain a high bioactive MLE.…”
Section: Mle Production By Enhanced Solvent Extractionmentioning
confidence: 99%
“…In the biomedical field, in particular, GPEs have demonstrated their anti-platelet and cardioprotective effects [3][4][5]. Sánchez-Gomar and coworkers [6] found that ethanolic and aqueous GPEs had pro-angiogenic and anti-apoptotic properties over endothelial colony-forming cells. Furthermore, the antiproliferative and pro-apoptotic properties of GPEs on certain cancerous cells were noticed by Caponio and coworkers [7].…”
Section: Introductionmentioning
confidence: 99%